Developing swimming skills in adults using applied swimming techniques - Artegov, P.D. (Theory and Practice of Physical Culture, 2026)
The results of the experiment confirmed the effectiveness of applied methods for teaching swimming to adult learners. In EG-1, the use of an individually differentiated approach in teaching adults ensured the development of swimming skills and psychological confidence. In EG-2, statistically significant positive changes were observed after the sessions in both endurance levels (Cooper test) and swimming technique quality.